KOMUNIKASI NON VERBAL DALAM PELAYANAN PRIMA DI UPTSA (UNIT PELAYANAN TERPADU SATU ATAP) PEMERINTAH KOTA SURABAYA - Maria Magdalena Hadipoero; Redi Panuju (Lingkar Studi Komunikasi (LISKI), 2018)
In this research, researchers focus on nonverbal communication such as eye contact, expressions, smilling, gesture, posture and gait, sitting, dress, makeup and hair styling, hand shaking, proximity, fragrance and voice and tones. All those elements as costomer guidelines in UPTSA service. Customer satisfaction is needed in every role which means applicants who apply licence in government city of Surabaya can have it on UPTSA at Siola Building Tunjungan streets 1-3, Surabaya. In addition , Excellence Service has two meanings, comprehension of service which related to product knowledge and service with related to good nonverbal communication to accomplish customer satisfaction. This research is describing how nonverbal communication can be affected in service communication in city of Surabaya licencees. Communication reference in this research is interpersonal communication with Qualitative descriptive method and case study by applying Harold Laswell’s theory. More over, the data assessed from employees and applicants interviews. Key Words : Nonverbal Communication, Service Excellence